SHP-2 deletion in postmigratory neural crest cells results in impaired cardiac sympathetic innervation - Lajiness, Jacquelyn D. (National Academy of Sciences, 2014)
Autonomic innervation is an essential component of cardiovascular regulation that is first established from the neural crest (NC) lineage in utero and continues developing postnatally. Although in vitro studies have indicated that SH2-containing protein tyrosine phosphatase 2 (SHP-2) is a signaling factor critical for regulating sympathetic neuron differentiation, this has yet to be shown in the complex in vivo environment of cardiac autonomic innervation. Targeting SHP-2 within postmigratory NC lineages resulted in a fully penetrant mouse model of diminished sympathetic cardiac innervation and concomitant bradycardia. Immunohistochemistry of the sympathetic nerve marker tyrosine hydroxylase revealed a progressive loss of adrenergic ganglionic neurons and reduction of cardiac sympathetic axon density in Shp2 cKOs. Molecularly, Shp2 cKOs exhibit lineage-specific suppression of activated phospo-ERK1/2 signaling but not of other downstream targets of SHP-2 such as pAKT. Genetic restoration of the phosphorylated-extracellular signal-regulated kinase (pERK) deficiency via lineage-specific expression of constitutively active MEK1 was sufficient to rescue the sympathetic innervation deficit and its physiological consequences. These data indicate that SHP-2 signaling specifically through pERK in postmigratory NC lineages is essential for development and maintenance of sympathetic cardiac innervation postnatally.